ORIENTASI TAFSIR ISYARI SUFI PADA TAFSIR AN NASAFY - Hermansyah (Dirasat: Journal Islamic Studies, 2025)
This study departs from the need to highlight the living and hidden dimension of Sufism behind the simplicity of the editorial of Tafs?r an-Nasaf? by 'Abdull?h ibn A?mad an-Nasaf?, a great scholar of M?tur?diyyah of the 7th century AH. So far, Tafs?r an-Nasaf? has often been positioned as a concise commentary that is on the rational-moderate path, but if examined more deeply, it will be found that the current of Sufism is prominent and significant in interpretation. Through a thematic and descriptive-qualitative analysis approach, this study found that the orientation of isy?r? Sufism in Tafs?r an-Nasaf? appeared prominent and significant. These elements are seen in: (1) the emphasis on moral-spiritual meaning after the presentation of zahir verses; (2) the use of Sufism terms such as ma'rifah, muj?hadah, tazkiyah al-nafs, and ?aq?qah; (3) the integration between the M?tur?diyyah theological framework and the Sufi inner consciousness; and (4) the association of the verses of the Qur'an with the process of the soul's journey to spiritual maturity. Thus, this study shows that Tafs?r an-Nasaf? is an important example of moderate Sufism—a Sufism that does not deny the text, does not ignore zahir, but instead makes spiritual experience a layer of meaning that deepens the understanding of shari'i. These findings provide an academic basis for expanding the study of the position of moderate isy?r? Sufism in the study of contemporary interpretation and its relevance to the development of a balanced modern Islamic spirituality rooted in the classical scientific tradition.